2020
DOI: 10.1016/j.heliyon.2020.e04029
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial analysis of traffic – Related pollutant under the influence of the seasonality and meteorological variables over an urban city in Peru

Abstract: A four yearlong air monitoring data (since 2015 to 2018) was collected to assess the impact of meteorological parameters such as temperature, relative humidity, wind speed and wind direction on the spatial and temporal variability of CO (carbon monoxide), NO 2 (nitrogen oxide), O 3 (ozone), SO 2 (sulfur dioxide), PM 10 and PM 2.5 (particulate matter with diameter aerodynamic less than 2.5 μm and 10 μm respectively) in Lima Metropolitan Area (LMA). Data from eight air quality monitoring stations, currently unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…They found that PM 2.5 concentrations at six of the ten regulatory monitors in Lima exceeded the World Health Organization (WHO) daily guideline on 77% of the days between 2014 and 2015. PM 2.5 concentrations in Lima show seasonal trends, with the highest levels observed in the summer (Romero et al, 2020b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that PM 2.5 concentrations at six of the ten regulatory monitors in Lima exceeded the World Health Organization (WHO) daily guideline on 77% of the days between 2014 and 2015. PM 2.5 concentrations in Lima show seasonal trends, with the highest levels observed in the summer (Romero et al, 2020b).…”
Section: Introductionmentioning
confidence: 98%
“…Vehicular emissions are the dominant source of pollution in the city (Arias Veĺasquez et al, 2019;Silva et al, 2017). The diurnal peaks of PM 2.5 during rush hours (Romero et al, 2020b;Sánchez Ccoyllo et al, 2011), as well as the association between proximity to roads and the concentrations of PM 2.5 and Black Carbon (BC) is evidence of this (Underhill et al, 2015). The government has attempted to mitigate vehicular pollution by phasing out lead from gasoline, reducing the sulfur content in diesel and reducing the permissible age of vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015 air pollution, in general, are responsible for over 6 million deaths in the world [10,11]. There is more than 400,000 premature death in Europe [12], and around 7 million worldwide [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 80.49% of emissions in Beijing, China, were produced by motor vehicles [14]. It was also found that 80% of air pollution in the Lima Metropolitan Area was produced from automobiles [13]. in China, 85% of emissions were from transport [15], while in the United Kingdom was 92% [16], and 75% in Malaysia [17], but in the United States, automobiles are responsible for emitting 57% of air pollution [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are relatively few studies on PM matter in many South American countries, including Peru. Those few studies investigating air quality in Peru have found extreme cases of air pollution due to limited atmospheric circulation in high altitude cities, lack of government oversight on large emission sources such as factories, and the prevalence of older vehicles still in use in many regions [6,20]. The city of Arequipa is an important industrial and commercial center of Peru with over 1 million residents.…”
Section: Introductionmentioning
confidence: 99%